A Regression-Based Patent Data Analysis Approach: A Case Study for Weapon Technology Evaluation Process - Altuntas, Serkan; Dereli, Turkay (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Technology evaluation is one of the most essential tasks for today's companies to make correct decisions that will increase their competitiveness. To date, numeroushave been made to address technology evaluation in the literature. Nevertheless, none of them have built a technology map or classified technologies based on their effects on the competitive power of a company in practice. To overcome the limitations of previous studies, a regression-based patent data analysis is proposed here for technology evaluation in this article. To this end, the proposed approach builds a technology map and classifies the technologies into four classes with respect to the technology effect ratio, namely 1) very high effect class, 2) high effect class, 3) medium effect class, and 4) low effect class. The technology evaluation of weapon technology in the defense industry has been conducted to show how the proposed approach works in real life. A good technology management strategy can be selected among available alternatives by decision makers and managers using the proposed approach. The results show that the proposed technology evaluation process can be used effectively in practice.
Keywords: Patents; Weapons; Defense industry; Data analysis; Linear regression; Companies; Market research; Linear regression model; patent analysis; technology evaluation; weapon technology; SOCIAL NETWORK ANALYSIS; KNOWLEDGE; FUTURE; FIRMS; PERFORMANCE; INNOVATION; DOCUMENTS; GROWTH; Business & Economics; Engineering